2008
DOI: 10.1002/acp.1418
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processes in comprehension of science texts: the role of co‐activation in confronting misconceptions

Abstract: In this paper, we investigate the effects of readers' incorrect knowledge on the on-line comprehension processes during reading of science texts, with an eye towards examining the conditions that encourage revision of such knowledge. We employed computational (Landscape Model) and empirical (think-aloud and reading times) methods to compare comprehension processes by readers with correct and incorrect background knowledge, respectively. Science texts were presented in either regular or refutation versions; Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
127
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(147 citation statements)
references
References 67 publications
9
127
0
11
Order By: Relevance
“…Second, readers displayed better memory for source information if the information was presented in conjunction with discrepant assertions, as compared to cases in which the sources agreed. This effect qualifies previous research that has demonstrated readers' enhanced memory for regions of texts conveying conflicting content information (Albrecht & O'Brien, 1993;Hakala & O'Brien, 1995;O'Brien & Myers, 1985;Tapiero & Otero, 1999). When texts imply that discrepant assertions are associated with two distinct and meaningful sources, readers instead display enhanced memory for source-content links.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…Second, readers displayed better memory for source information if the information was presented in conjunction with discrepant assertions, as compared to cases in which the sources agreed. This effect qualifies previous research that has demonstrated readers' enhanced memory for regions of texts conveying conflicting content information (Albrecht & O'Brien, 1993;Hakala & O'Brien, 1995;O'Brien & Myers, 1985;Tapiero & Otero, 1999). When texts imply that discrepant assertions are associated with two distinct and meaningful sources, readers instead display enhanced memory for source-content links.…”
Section: Discussionsupporting
confidence: 43%
“…Supplemental measures have suggested that increased reading times indicate, above and beyond merely noticing a discrepancy, readers' attempts to selectively retrieve and reprocess information from long-term memory that contradicted the target sentence. Strong evidence for this is that readers exhibit enhanced memory for the regions of texts conveying conflicting content, more than for other previously read sentences (Albrecht & O'Brien, 1993;Baker & Anderson, 1982;Hakala & O'Brien, 1995;O'Brien & Albrecht, 1992;O'Brien & Myers, 1985;Tapiero & Otero, 1999). Verbal protocol evidence supports the idea that readers frequently attempt to resolve the two contradictory statements.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…Para lograr esta representación, el lector debe conectar ideas provenientes de diferentes partes del texto e integrarlas (Abusamra, & Joanette, 2012), esto es, debe realizar inferencias y conexiones entre la información literal explícita (Elbro & Buch-Iversen, 2013;van den Broek & Kendeou, 2008). La generación de inferencias se refiere a la activación de información que no se encuentra explícitamente enunciada durante la lectura para dar mayor coherencia a la oración focal que se está leyendo (Carlson et al, 2014;Freed & Cain, 2016;van den Broek, Risden, Fletcher, & Thurlow, 1996).…”
Section: Introductionunclassified